Jurnal Kata: rick riordans intention in writing percy jackson and lightning thief and the reception of the readers - Mugijatna, Sri kusumo hapsari: Yunita ariani putri (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
this research studies percy jackson and lightning thief by rick riordan